Antimicrobial activities of mycoleptodiscin B isolated from endophytic fungus Mycoleptodiscus sp. of Calamus thwaitesii Becc. - Ranga K. Dissanayake, Pamoda B. Ratnaweera & & , David E. Williams, C. Dilrukshi Wijayarathne, Ravi L. C. Wijesundera, Raymond J. Andersen, E. Dilip de Silva (Journal of Applied Pharmaceutical Science, 2016)
Endophytic fungi are a promising source of novel biologically active compounds including antimicrobials. Plant endophytic fungi of Sri Lanka, an island with exceptionally high biodiversity and endemism, are a vastly untapped resource. Therefore this study was initiated with the objective of examining the antimicrobial producing potential of the endophytic fungi of Calamus thwaitesii Becc. from Sri Lanka. This examination resulted in the isolation of 21 fungi with 7 of them exhibiting antimicrobial properties. Further investigation of the Mycoleptodiscus sp. isolated from the leaves, which showed the best activity among them, resulted in the isolation of the known alkaloid mycoleptodiscin B and its structure was elucidated and confirmed by mass and nuclear magnetic resonance spectral data. Mycoleptodiscin B showed promising antimicrobial activity against Bacillus subtilis (MIC 0.5 µg mL-1) and Staphylococcus aureus (MIC 1 µg mL-1), and was less potent against methicillin resistant Staphylococcus aureus (MRSA, MIC 32 µg mL-1) and the pathogenic fungus Candida albicans (MIC 64 µg mL-1). This is the first study to report the isolation, identification and antimicrobial properties of endophytic fungi of C. thwaitesii and the antimicrobial activities of the alkaloid mycoleptodiscin B.
Keywords: Mycoleptodiscus sp., Calamus thwaitesii, mycoleptodiscin B, endophytic fungus, antimicrobial.